In vitro and in vivo Biological Responses to Graphene and Graphene Oxide: A Murine Calvarial Animal Study - Chang TK (Dove Medical Press, 2020)
Ting-Kuo Chang,1–3,* Yung-Chang Lu,1–3,* Shu-Ting Yeh,2,3 Tzu-Chiao Lin,2,3 Chun-Hsiung Huang,2–4 Chang-Hung Huang1–3,5 1Department of Medicine, MacKay Medical College, New Taipei City, Taiwan; 2Department of Orthopaedic Surgery, MacKay Memorial Hospital, Taipei, Taiwan; 3Department of Medical Research, MacKay Memorial Hospital, Taipei County, Taiwan; 4Department of Orthopaedic Surgery, Changhua Christian Hospital, Changhua, Taiwan; 5Department of Dentistry, National Yang-Ming University, Taipei, Taiwan*These authors contributed equally to this workCorrespondence: Chang-Hung HuangDepartment of Medical Research, MacKay Memorial Hospital, No. 45, Minsheng Road, Tamshui District, New Taipei City, TaiwanEmail changhung0812@gmail.comBackground: Graphene and its derivatives have recently gained popularity in the biomedical field. Previous studies have confirmed that both the mechanical strength and wear resistance of graphene-containing polyethylene have been greatly improved. Therefore, it is being considered as an alternative for artificial joint replacement liners. Based on the literature, the wear debris generated from the traditional polymers used for orthopedic liners could lead to particle-induced osteolysis and, consequently, failure of joint replacement. However, the biological response of this novel graphene-based polymer is still unclear. Therefore, the current study aimed to investigate the in vitro and in vivo biological effects of graphene and graphene oxide (GO) particles on bone.Materials and Methods: The biological responses of graphene and GO particles were tested via in vitro and murine calvarial in vivo models. In the in vitro model, murine macrophage cells were mixed with particles and hydrogel and printed into two differently designed scaffolds; the induced proinflammatory cytokines were then tested. In the murine in vivo model, the particle size distribution was measured via SEM, and these particles were then administrated in the calvarial area, referring to our established model. A micro-CT and histological analysis were performed to examine the biological effects of the particles on bone health. The data were analyzed via the one-way analysis of variance to determine the differences between the groups.Results: Both graphene and GO induced significantly higher TNF-α and IL-6 secretion compared with the control in the three-dimensional in vitro model. In the murine calvarial in vivo test, the graphene and GO particles increased the bone mass compared with the sham groups in the micro-CT analysis. Bone formation was also observed in the histological analysis.Conclusion: In these in vivo and in vitro studies, the graphene and GO wear debris did not seem to induce harmful biological response effect to bone. Bone formation around the skull was observed in the calvarial model instead. Graphene-containing biomaterials could be a suitable new material for application in orthopedic prostheses due to their benefit of eliminating the risk of particle-induce osteolysis.Keywords: biological response, graphene, graphene oxide, osteolysis, osteogenesis